STRATEGI GURU PAI DALAM MENANAMKAN KEBIASAAN SHALAT BERJAMA’AH UNTUK MENINGKATKAN KEDISIPLINAN SISWA DI SMP ISLAM AL AKBAR SINGOSARI - Rizki Akbar Aqilla; Muhammad Hanif; Moh. Eko Nasrullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to describe the strategy of PAI teachers in instilling the habit of praying in congregation in students at Al Akbar Islamic Junior High School Singosari. The problem in this research is the planning, implementation, and evaluation of PAI teachers in instilling the habit of praying together to improve student discipline at Al Akbar Islamic Junior High School Singosari. The researcher uses a phenomenological-based qualitative approach with the type of case study research. The results of this study indicate that PAI teachers have an important role in accustoming students to praying in congregation, praying in congregation can improve student discipline by using several methods carried out by PAI teachers, namely the teacher being an example for all students in praying in congregation at school, habituation students enter early to perform congregational prayers at school, through the method of understanding by providing good values contained in the habit of praying in congregation, with the school rules, the teacher can provide direction and supervision to students related to discipline, and evaluation is carried out once a month with the aim of improving the activities carried out by the school.